Construção e calibração de tubos de permeação - Cardoso, Arnaldo Alves [UNESP]; Locateli, Ana Flávia [UNESP]; Carloni Filho, João [UNESP]; Franco, Reinaldo [UNESP] (My University, 1996)
A dynamic system for stablishing a known standard gas mixture is necessary for many studies such as development and testing of analytical methods. A permeation tube can be used for this purpose. The work described here shows the construction, operation and calibration of a simple permeation tube which can be used to obtain large amounts of a standard gas.
Contruction and calibration of permeation tubes
Keywords: Permeation tube; Standard gas analysis; Standard gas generation; Test atmospheres